2001
DOI: 10.4049/jimmunol.166.2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Is a Negative Feedback Regulator of Nitric Oxide Synthesis in Murine Macrophages

Abstract: In a system of endotoxin (LPS)-mediated NO production in ANA-1 murine macrophages, suppression subtractive hybridization was used to identify genes up-regulated by NO. Osteopontin (OPN), a secreted acidic phosphoprotein that binds to a cell surface RGD integrin-binding motif, was found to be differentially expressed in the presence of NO. OPN has been demonstrated to inhibit NO production in a variety of cell types. Northern blot and nuclear run-on analyses demonstrated that OPN mRNA levels and gene transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 28 publications
4
94
0
5
Order By: Relevance
“…A siRNA MM with limited homology to mouse genes served as the siRNA-negative control. As we and others (2,(12)(13)(14) have previously demonstrated, LPS induced iNOS, Tap1, and OPN protein expression in RAW264.7 cells. Ablation of OPN expression with siRNA in the presence of LPS was associated with a 6-fold increase iNOS and Tap1 protein in comparison to LPS alone ( p Ͻ 0.01 LPS vs LPSϩsiRNA OPN).…”
Section: Opn Inhibition Of Inos and Tap1 Protein And Mrna Expressionsupporting
confidence: 75%
See 1 more Smart Citation
“…A siRNA MM with limited homology to mouse genes served as the siRNA-negative control. As we and others (2,(12)(13)(14) have previously demonstrated, LPS induced iNOS, Tap1, and OPN protein expression in RAW264.7 cells. Ablation of OPN expression with siRNA in the presence of LPS was associated with a 6-fold increase iNOS and Tap1 protein in comparison to LPS alone ( p Ͻ 0.01 LPS vs LPSϩsiRNA OPN).…”
Section: Opn Inhibition Of Inos and Tap1 Protein And Mrna Expressionsupporting
confidence: 75%
“…M acrophage-inducible NO synthase (iNOS) 3 expression is central to many of the systemic effects associated with endotoxin (LPS) stimulation (1). Using both in vivo and in vitro murine models of endotoxin (LPS) stimulation, we have previously demonstrated that NO feedback inhibits its own synthesis by increasing transcription of osteopontin (OPN), a potent transrepressor of iNOS expression (2)(3)(4). OPN transcription and promoter activity are significantly up-regulated in response to NO in LPS-stimulated ANA-1 and RAW264.7 murine macrophages (5).…”
mentioning
confidence: 99%
“…However, the converse relationship, the role of NO in the induction of OPN synthesis, has not been well studied. We have previously found that LPS induced NO synthesis up-regulates OPN promoter activity and protein expression (3). In this study, we provide evidence that S-nitrosylation of hnRNP A/B inhibits DNA binding activity to the OPN promoter.…”
Section: Discussionsupporting
confidence: 52%
“…Studies indicate that the OPN promoter contains various motifs including a purine-rich sequence, an Ets-like sequence, glucocorticoid and vitamin D response elements, and interferon-inducible elements (1,2). In this regard, we have previously demonstrated that OPN transcription and promoter activity are significantly up-regulated in response to NO in a system of endotoxin-stimulated murine macrophages (3). However, the specific cis-and trans-regulatory elements that determine the extent of endotoxin-and NO-mediated induction of OPN synthesis are unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation